The Flight from Rome [videorecording] - Dault, Gary Michael; Garwood, Joseph J.; McGreevy, John; Puncher, Jennifer; Ustinou, Peter Sir (Inside the Vatican, 1993)
Gripped by darkness and turmoil, Europe was hungry for a spiritual awakening. Travel the continent with Sir Peter and observe how Christianity answered the call. Meet Charlemagne, the englightened monarch who embraced the Christian faith, and St. Francis of Assissi who founded the Franciscan orders. Introduces also St. Catherine of Sienna, the nun whose miraculous vision brought the papacy back to Rome.